Governing the multicultural city-region - Frisken, Frances; Wallace, Marcia (2003)
This article reports on a study that identified the challenges posed by large immigrant populations for the governments of eleven Greater Toronto Area municipalities and the way those challenges were being addressed by municipal agencies that provided nine local services: government-assisted housing, land-use planning, policing, public education, public health, public libraries, public recreation, public transit, and social services. Many of the agencies were trying to accommodate their multicultural clienteles in a variety of ways. There were large differences in agency responses, however, not only among municipalities but also among agencies providing different services within the same municipality, and even among district offices of the same municipal agencies. Moreover, municipal agencies often found it difficult or impossible to adapt to new clienteles, even when they were seriously committed to doing so, in the face of provincial government indifference, cuts in provincial and local funding, and community ambivalence or antagonism. The study concluded that municipal agencies are unlikely to devote many resources to helping the immigrant settlement process without financial and legislative support from central governments. - Reproduced.
Keywords: Local government